(untitled) (Communication & Society, 1998)
This article analyzes the advertising of social causes promoted by non-governmental organizations from the point of view of the contents of messages. The author proposes certain guidelines and criteria in order to elaborate arguments to reach the target audience and to mold public opinion. Taking into account the nature of NGO and their objectives, the author proposes to apply the logic of relational marketing to the communication strategy of these organizations with the aim of attainings table and satisfactory relationships with their donors. In order to achieve this, the author suggests the use of rational arguments in the consolidation of relations between the organization and its donors, leaving the emotional arguments as a mere tactical resource in order to draw the attention of the audience.